Резонансні властивості та магнітна анізотропія нанокристалічного сплаву Fe73Cu1Nb3Si16B7 - Pogorily, A. M.; Polishchuk, D. M.; Tovstolytkin, A. I.; Kravets, A. F.; Zamorskyi, V. O.; Nosenko, A. V.; Nosenko, V. K. (Publishing house "Academperiodika", 2019)
Resonance properties of nanocrystalline ribbons of Fe73Cu1Nb3Si16B7 alloy annealed with the use of an electric current under a tensile stress of 180 MPa have been studied within the ferromagnetic resonance method. Two kinds of ferromagnetic regions with different anisotropic behaviors that coexist in the alloy after the annealing are detected. One of them is amorphous and weakly magnetically anisotropic, whereas the other is characterized by a pronounced uniaxial magnetic anisotropy and corresponds to the nanocrystalline phase. Quantitative estimations of magnetic parameters in two magnetic phases of the alloy are made.